Pengaruh Minat dan Gaya Belajar Terhadap Kemampuan Menghafal Alquran Siswa Program Tahfizh - Aniah, Siti; Darmayanti, Nefi; Arsyad, Junaidi (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine and describe: (1) The effect of interest on the ability to memorize the Koran for students of the Tahfizh program at SMP Shafiyyatul Amaliyyah Medan (2) The effect of learning styles on the ability to memorize the Koran for students at the Tahfizh program at SMP Shafiyyatul Amaliyyah Medan (3) The influence of interest and learning style on the ability to memorize the Koran for students of the Tahfizh program at SMP Shafiyyatul Amaliyyah Medan. This research was carried out at the Shafiyyatul Amaliyyah Middle School in Medan, especially in the Tahfizh program class. This research is a quantitative study with a population of all Tahfizh program students consisting of 6 classes with a total of 93 students. The research sample is the entire population (total sampling). The data collection instruments used were questionnaires and tests. The data analysis used simple and multiple linear regression. The findings showed: (1) There is a positive and significant effect of interest on the ability to memorize the Koran with a contribution of 4.6% with the equation of the regression line Y = 79,786 + 0,087, (2) there is an influence of each -each learning style on students' ability to memorize the Koran, with details of the percentage of contributions as follows; visual learning style contributed 9.2%, auditory learning style reached 1.7% and kinesthetic learning style 0.00%. The learning style of students that is more dominant in influencing the ability to memorize the Koran is the visual learning style, which is equal to 9.2%. (3) There is an influence of interest and learning style on the ability to memorize the Koran together with a contribution of 5.3% with the regression line equation Y = 77.281 + 0.068X_1 + 0.037X_2+ e.